All Days 2016
DOI: 10.2118/182234-ms
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation in High Water-Cut Wells: Treatment Optimization Using a Fluid Placement Model

Abstract: This work discusses application of an advanced placement model for optimizing stimulation treatments in high water-cut wells. Stimulation treatments in high water-cut wells are challenging because they can lead to an undesired increase in water production. Associative polymers have been successfully used as diverters for addressing this challenge, and effective treatments have been performed based on experience and guidelines. However, further optimization of such treatments can be achieved using fluid placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As the RPM injection rate increases, the adsorption amount and the adsorption hydrodynamic thickness gradually increase, consequently causing more permeability reduction. ,, It has been reported that extensional flows can stretch and orientate the chains/macromolecule of flexible polymers (such as polyacrylamide and poly­(ethylene oxide)). This is also called shear-induced elongation. ,, Polymer molecules can be imagined as entangled coils.…”
Section: Polymer Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the RPM injection rate increases, the adsorption amount and the adsorption hydrodynamic thickness gradually increase, consequently causing more permeability reduction. ,, It has been reported that extensional flows can stretch and orientate the chains/macromolecule of flexible polymers (such as polyacrylamide and poly­(ethylene oxide)). This is also called shear-induced elongation. ,, Polymer molecules can be imagined as entangled coils.…”
Section: Polymer Adsorptionmentioning
confidence: 99%
“…Wall effects have been recognized as an important post-treatment factor. Generally, it is agreed that wall effects appear due to the presence of the layer of the adsorbed polymer on the pore walls. , ,,,,,,, The wall effect of RPMs can cause a noticeable reduction to water relative permeability but a minimum effect on oil/gas relative permeability due to the physical or chemical properties of the adsorbed layer . It is claimed that the wall effect is expected to induce one or a combination of subeffects that altogether determine the outcome of RPM treatment, and these include the following:…”
Section: Postadsorption Mechanismsmentioning
confidence: 99%